Sustainable irrigation development - Makin, Ian W. (2004)
This paper explores the issues that face irrigation in the future, drawing on recent experiences in Asia and elsewhere to illustrate some cases where interventions have fallen short of sustainable development targets. The paper argues that sustainable development is often misinterpreted and that incremental development is a more realistic model to achieve the objectives of sustainability and poverty alleviation. In the paper the focus is on irrigation as a means of achieving food security. However, effective utilization of water to achieve high productivity is a major objective, and this is now widely recognized to include enhanced rainfed agriculture and agricultural system. Therefore, the boundaries between rainfed and irrigated agriculture are becoming increasingly blurred requiring practitioners in agricultural development to have a broader perspective. The use of sustainable livelihood concepts has also changed the development canvas by bringing the analysis of the entire socioeconomic setting into focus.